Childhood obesity prevention in Texas : workshop summary - Burns, Annina Catherine; Nyberg, Kara (Kara A.); Parker, Lynn (Online access: NCBI NCBI Bookshelf., 2009)
"Childhood Obesity Prevention in Texas summarizes the information gathered at a workshop held February 5-6, 2009, in Austin, Texas. At this workshop, committee members met with Texas lawmakers, public officials, and community leaders to exchange ideas and to view first-hand strategies that are being implemented effectively at the state and local levels to prevent and reverse childhood obesity. Texas leaders at the workshop expressed the strong belief that the state's economic vitality and security depend on the health of its population. Accordingly, the state is no longer simply describing the personal, community, and financial costs of its obesity crisis; it is taking proactive steps to address the problem through strategic initiatives. An overarching strategy is to address obesity by targeting the state's youth, in whom it may be possible to instill healthy behaviors and lifestyles to last a lifetime. A guiding principle of these efforts is that they should be evidence based, community specific, sustainable, cost-effective, and supported by effective partnerships. Moreover, the goal is for the responsibility to be broadly shared by individuals, families, communities, and the public and private sectors."--Publisher's website